Water Challenges in Kabul River Basin - Safi, Abdul Ghias; Reshteen, Sediqullah (Journal of Natural Sciences – Kabul University, 2022)
Water scarcity and its extinction in a geographical area creates significant challenges and threats to all human and all living beings, therefore water is an essential element for survival and sustainability. Over the past four decades, water resources have been severely damaged in many parts of the Kabul watershed due to rapid population growth, mismanagement of water, environmental problems, climate change, air pollution and other factors, is drying up. This article provides a brief overview of the water challenges in the Kabul watershed, collects perennial data on climate change, especially climate change and rainfall, and conducts comprehensive research and evaluation. At the end of the article, the problems, losses and appropriate solutions to the problems in the field are mentioned.